3D‐Printed Scanning‐Probe Microscopes with Integrated Optical Actuation and Read‐Out. Issue 2 (5th December 2019) - Dietrich, Philipp‐Immanuel; Göring, Gerald; Trappen, Mareike; Blaicher, Matthias; Freude, Wolfgang; Schimmel, Thomas; Hölscher, Hendrik; Koos, Christian
Abstract: Scanning‐probe microscopy (SPM) is the method of choice for high‐resolution imaging of surfaces in science and industry. However, SPM systems are still considered as rather complex and costly scientific instruments, realized by delicate combinations of microscopic cantilevers, nanoscopic tips, and macroscopic read‐out units that require high‐precision alignment prior to use. This study introduces a concept of ultra‐compact SPM engines that combine cantilevers, tips, and a wide variety of actuator and read‐out elements into one single monolithic structure. The devices are fabricated by multiphoton laser lithography as it is a particularly flexible and accurate additive nanofabrication technique. The resulting SPM engines are operated by optical actuation and read‐out without manual alignment of individual components. The viability of the concept is demonstrated in a series of experiments that range from atomic‐force microscopy engines offering atomic step height resolution, their operation in fluids, and to 3D printed scanning near‐field optical microscopy. The presented approach is amenable to wafer‐scale mass fabrication of SPM arrays and capable to unlock a wide range of novel applications that are inaccessible by current approaches to build SPMs. Abstract : 3D‐printed scanning‐probe microscopy (SPM) engines offer a tremendous freedom of design allowing the integration of several measurement principles in one monolithic structure, which includes excitation and read‐out already. Atomic force microscopy with atomic‐scale step‐height resolution as well as scanning near‐field optical microscopy characterizing active and passive optical elements is demonstrated. Wafer‐level fabrication of massively SPM arrays is possible.